"Appreciation" (translated by Jerry Mirskin and Michel Sirvent) - Jean Ricardou (Studies in 20th & 21st Century Literature, 1991)
Appreciation (translated by Jerry Mirskin and Michel Sirvent)
Keywords: Appreciation; Jerry Mirskin; Michel Sirvent; translation; translator